2013
DOI: 10.1002/14651858.cd003303.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Reading aids for adults with low vision

Abstract: Differences Between Protocol And Review: 2013 update: •We decided to remove the RCT filter from the electronic searches in order to identify as many potentially relevant studies as possible. We also specified that reading speed had to be measured at ordinary print size because this is the outcome most relevant to patients in terms of performance using a specific low-vision aid. We also specified that MNREAD definitions of maximum reading speed and reading acuity were adopted in our review and the consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 63 publications
0
56
0
3
Order By: Relevance
“…A standard LogMAR chart is used to determine the best possible visual acuity in each eye to test central visual acuity [34]. The best-corrected visual acuity measurements of SLE and SS patients were within the normal range (0.0 ± 0.1 log and 0.0 ± 0.1 log, respectively) and similar to those in HC (0.0 ± 0.1 log).…”
Section: Resultsmentioning
confidence: 99%
“…A standard LogMAR chart is used to determine the best possible visual acuity in each eye to test central visual acuity [34]. The best-corrected visual acuity measurements of SLE and SS patients were within the normal range (0.0 ± 0.1 log and 0.0 ± 0.1 log, respectively) and similar to those in HC (0.0 ± 0.1 log).…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in reading speed could be explained by reduced visual span, or by image movement. A 2018 review of studies evaluating reading aids for people with low vision found that reading speed may be highest in stand‐mounted electronic CCTVs compared to optical devices, with further evidence for longer reading durations and better ease of use . Comparing stand‐mounted CCTVs and head‐mounted devices (HMDs), the review reported similar performance between the two: for HMDs, on average 66 words per minute and near visual acuity of 0.92 logMAR; for CCTVs, 3.1 words per minute more for reading speed and 0.05 logMAR more for near visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organisation criteria for defining visual ability (Virgili et al . ), most dogs in this study would be classified as having poor vision. While the apparent lack of any visual impairment in all dogs assessed may be attributed to the paucity of appropriate measures of vision in domestic animal species, it is essential to consider the other components of vision, and that the relative importance of these factors varies considerably between species.…”
Section: Discussionmentioning
confidence: 94%